Beyond Six Sigma – A Control Chart for Tracking Defects per Billion Opportunities (dpbo) - Santos, Daryl (International Journal of Industrial Engineering: Theory, Applications and Practice, 2009)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> <!--StartFragment--> In many processes and, in particular, those related to electronics packaging and assembly, the amount of possible defect counts per unit of product has become quite large. Because the classical attributes-based statistical process control (SPC) charts where defects are measured in counts – the u chart and c chart, for examples – were cumbersome to cope with such large scale defect possibilities, a defects per million opportunities (dpmo) chart was developed in the mid 1990s. Not long after this, it was mentioned by a researcher at Packard Bell that “world-class” in surface mount technology (SMT) – an assembly technique for electronics manufacturing – should indicate that the company is operating at 50ppm (or fewer) defect levels and suggested that the number could drop to 10ppm. Furthermore, it was hypothesized that the electronics industry may one day refer to defect levels in terms of parts-per-billion (ppb) – defect levels reflective of process capabilities better than six sigma levels. With this in mind, this paper presents a new control chart for attributes data measured in counts where the plot point per period is represented by defects per billion opportunities (dpbo). In addition to showing the plot point and control chart calculations, an example will be provided and analyzed to demonstrate its use. <!--EndFragment-->